Organic Transformations Mediated by Weak Non-Covalent Interactions - Sahoo, Sathi; Kumar Dinda, Tarun; Mal, Prasenjit (Synlett)
Since its formal inception following the 1987 Nobel Prize awarded to Cram, Lehn, and Pedersen, supramolecular chemistry has evolved into a cornerstone of modern molecular science, driven by the strategic use of noncovalent interactions like hydrogen bonding, halogen bonding, π-stacking, and beyond. These subtle yet powerful forces enable the construction of adaptive, stimuli-responsive architectures with exceptional spatial and functional precision. In the realm of catalysis, such interactions unlock new dimensions of control: they preorganize reactive species, stabilize elusive transition states, and steer reaction pathways with unmatched selectivity. This feature article surveys recent breakthroughs in organic supramolecular catalysis, emphasizing how π-stacking, electron donor-acceptor (EDA) complexation, and anion-π interactions are being ingeniously leveraged to drive high-efficiency transformations under mild, often metal-free, conditions. By integrating innovative design principles with mechanistic insight, we propose a forward-looking vision for supramolecular catalysis, not merely as a toolkit, but as a foundational paradigm poised to revolutionize the future of sustainable organic synthesis.